2019
DOI: 10.1016/j.matt.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Transparent Teeth of the Deep-Sea Dragonfish, Aristostomias scintillans

Abstract: Deep-sea fishes living in darkness have evolved unique predation and communication mechanisms involving bioluminescence and other stratagems. Another adaptation is the transparency of the teeth of several species, which is hypothesized to provide stealth for predation. We investigated the transparent teeth of the dragonfish and discovered that it is due to the mixture of nanocrystalline and amorphous phases in both its enamel-like and dentin layers and the absence of tubules. This structure significantly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Many fish larvae have transparent bones, and part of the cranium of barreleye fish remains transparent during their lifetime, but the underlying physical principles are poorly understood (Robison and Reisenbichler, 2008) [62]. It was shown that the heavily mineralized teeth of the deep-sea dragonfish remain unusually transparent (in order to optically trick their prey), as they have special nanostructured dentin consisting of a woven pattern of nanometer rods (5 nm in diameter with 0.8 nm spacing) that nearly eliminates light scattering (Velasco-Hogan et al, 2019) [95]. This may be the key to engineering bone clearing in vivo—to discover how it happens naturally in fish.…”
Section: In Vivo Transparency Of Bones and Other Mineralized Tissuementioning
confidence: 99%
“…Many fish larvae have transparent bones, and part of the cranium of barreleye fish remains transparent during their lifetime, but the underlying physical principles are poorly understood (Robison and Reisenbichler, 2008) [62]. It was shown that the heavily mineralized teeth of the deep-sea dragonfish remain unusually transparent (in order to optically trick their prey), as they have special nanostructured dentin consisting of a woven pattern of nanometer rods (5 nm in diameter with 0.8 nm spacing) that nearly eliminates light scattering (Velasco-Hogan et al, 2019) [95]. This may be the key to engineering bone clearing in vivo—to discover how it happens naturally in fish.…”
Section: In Vivo Transparency Of Bones and Other Mineralized Tissuementioning
confidence: 99%
“…From all of the above one can infer that challenges are to be positively accepted. Form follows function [54] and this is why nature defined the evolution of species, as species undergo adaptive changes [55] . A quick look into different species heart morphology allows to understand why the heart has different forms and sizes [56] .…”
Section: The Intellectual Componentmentioning
confidence: 99%
“…In addition to cornea and fish scales 14 , transparent collagen matrices were recently reported in natural tissues, i.e. elephant ivory 15 and teeth of the deep-sea dragonfish 16 , and in synthetic collagen scaffolds 17 . Transparency of such heterogeneous complex materials remains an intriguing property.…”
mentioning
confidence: 99%